Gynecologic Cancer InterGroup (GCIG) Consensus Review for Ovarian Tumors of Low Malignant Potential (Borderline Ovarian Tumors). (1st November 2014) - Harter, Philipp; Gershenson, David; Lhomme, Catherine; Lecuru, Fabrice; Ledermann, Jonathan; Provencher, Diane M.; Mezzanzanica, Delia; Quinn, Michael; Maenpaa, Johanna; Kim, Jae-Weon; Mahner, Sven; Hilpert, Felix; et al.
Abstract : Abstract: Since the early 1970s, the World Health Organization and the International Federation of Gynecology and Obstetrics have classified borderline ovarian tumors as an independent group of ovarian epithelial tumors. A consensus statement of the Gynecologic Cancer Intergroup is reported.